Assessment of the breakdown products of solar/UV induced photolytic degradation of food dye tartrazine - Santos, Tuane Cristina dos [UNESP]; Zocolo, Guilherme Juliao [UNESP]; Morales, Daniel Alexandre; Umbuzeiro, Gisela de Aragao; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2014)
The food dye tartrazine (CI 19140) was exposed to UV irradiation from an artificial source, a mercury vapor lamp, and a natural one, sunlight. It was observed that conditions such as energy dose, irradiation time, pH and initial dye concentration affected its discoloration. There was 100% of color removal, after 30 min of irradiation, when a dye solution 1 x 10(-5) mol L-1 was submitted to an energy dose of 37.8 J cm(-2). Liquid Chromatography coupled to Diode Array Detection and Mass Spectrometry confirmed the cleavage of the chromophore group and the formation of five by-products at low concentration. Although by-products were formed, the Salmonella/microsome mutagenicity assay performed for both, the dye solution at a dose of 5.34 mg/plate and the solutions obtained after exposure to UV irradiation, did not present mutagenic activity for TA98 and TA100 with and without S9. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Dye photolysis; Tartrazine; Breakdown products; Mutagenicity; LC-MS/MS